2013
DOI: 10.1521/soco_2012_1005
|View full text |Cite
|
Sign up to set email alerts
|

When Black Sheep Make us Think: Information Processing and Devaluation of In- and Outgroup Norm Deviants

Abstract: since group membership is central for a person's identity, providing norms, values, and beliefs, people devalue ingroup deviants more than outgroup deviants. This so-called black-sheep effect (Bse) seems primarily driven by group-based motivational concerns. given prior evidence that information about ingroup, in comparison to outgroup members, is processed more systematically, we propose that more systematic processing of ingroup information predicts more ingroup deviant devaluation. Thus differences in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
2
18
0
2
Order By: Relevance
“…However, a similar but completely opposite phenomenon of ingroup favoritism has also been reported in the study of intergroup bias, a phenomenon called ingroup derogation [ 37 – 48 ]. Results showed that, when participants were from the inferior social groups [ 37 – 39 ], or from East Asian cultures [ 40 44 ], or when the targets were deviant ingroup members [ 45 48 ], participants showed a preference to and affinity for outgroup members instead of ingroup members. This strange anti-us behavioral tendency was particularly prevalent in East Asian cultures [ 40 44 , 49 54 ].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, a similar but completely opposite phenomenon of ingroup favoritism has also been reported in the study of intergroup bias, a phenomenon called ingroup derogation [ 37 – 48 ]. Results showed that, when participants were from the inferior social groups [ 37 – 39 ], or from East Asian cultures [ 40 44 ], or when the targets were deviant ingroup members [ 45 48 ], participants showed a preference to and affinity for outgroup members instead of ingroup members. This strange anti-us behavioral tendency was particularly prevalent in East Asian cultures [ 40 44 , 49 54 ].…”
Section: Introductionmentioning
confidence: 61%
“…Such a mechanism should also follow the smoke detector principle and the functional flexibility principle. Then, ingroup derogation should not only exist in actual social groups [ 37 – 48 ]. Mere social categorization alone—a heuristic cue that implies the differentiation between "us" and "them" [ 59 , 60 ]—should be sufficient to produce this bias (i.e., smoke detector principle), which should be particularly stronger when the individuals feel vulnerable to diseases, when there are cues of diseases in the immediate physical environment, or when there are people who display disease cues in the immediate social environment (i.e., functional flexibility principle).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, future research could investigate ingroup reactions to self-disclosure in relation to the group's cultural context; some groups may be more careful to protect their public image than others, which would result in different evaluations of honest ingroup disclosures that threat the positivity of that image. Finally, future studies could examine whether the central and peripheral information processing routes (Petty & Cacioppo, 1986;Reese et al, 2013) could account for the differences in the evaluations of ingroup or outgroup moral people who threat the group's positive identity.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the emergence of the black sheep effect concerns differences in the elaboration https://doi.org/10.1016/j.soscij.2018.07.003 0362-3319/© 2018 Published by Elsevier Inc. on behalf of Western Social Science Association. of information regarding deviant members of ingroups and outgroups (Reese, Steffens, & Jonas, 2013). According to Reese et al (2013), judgments of ingroup deviant members requires systematic processing while outgroup deviant behaviour is evaluated using heuristic processing (ELM, Petty & Cacioppo, 1986) and this difference may account for the differences in judgment (more or less extreme).…”
mentioning
confidence: 99%
“…Research on moral credentials proves that a group's good deeds can be added to an individual's moral account (Kouchaki, 2011). For the sake of protecting the group's positive image (Reese et al, 2013) it will not punish any member who commits a moral offence by the Devil Protection Effect (DPE) (Stratton, 2007).…”
Section: Previous Studiesmentioning
confidence: 99%